Symptom-Based Management of Chronic Gastroesophageal Reflux Disease in a Young Adult: A Holistic Therapeutic Approach - Rhomy Leokrisnha; Anggunan; M Raihan Raid Ijlal; Maisa Aqila Fazilatun Nisa; Marisha Alsahda Hr; Mely Shanrina Br Regar; Mentari Kusuma Putri (CV. FOUNDAE, 2025)
Gastroesophageal Reflux Disease (GERD) is a chronic gastrointestinal disorder resulting from the retrograde movement of gastric contents into the esophagus, often due to lower esophageal sphincter dysfunction. It is characterized by hallmark symptoms such as heartburn, regurgitation, epigastric pain, and may also present with extra-esophageal manifestations including chronic cough, hoarseness, or dental erosion. GERD significantly affects quality of life and, if left untreated, may lead to complications such as esophagitis, strictures, or Barrett’s esophagus. This case report presents a 21-year-old female with a history of recurrent GERD symptoms since childhood. She presented with complaints of persistent epigastric pain, nausea, and a burning sensation in the chest, particularly after meals. Physical examination revealed epigastric tenderness and clinical signs suggestive of anemia, including pallor and fatigue. A detailed clinical history and symptom pattern strongly supported a diagnosis of GERD. Given the classic presentation and absence of alarm features, a non-invasive, symptom-based diagnostic approach was adopted, avoiding the need for endoscopy or pH monitoring. The patient was managed with a combination of pharmacological therapy omeprazole (a proton pump inhibitor), antacids for symptomatic relief, paracetamol for pain management, and vitamin B6 to address nutritional deficiencies. Additionally, lifestyle modifications were emphasized, including dietary regulation, avoidance of trigger foods (such as spicy and acidic items), elevation of the head during sleep, and meal timing adjustments. Within one week of initiating treatment, the patient reported significant improvement in symptoms, with reduced frequency and intensity of heartburn and nausea. This case highlights the importance of early recognition and comprehensive management of GERD, especially in young adults with a chronic history of symptoms. It underscores the effectiveness of combining pharmacological treatment with lifestyle interventions and demonstrates that a symptom-based, non-invasive approach can be both practical and effective in primary care settings. Patient education and adherence to therapy remain critical in preventing recurrence and improving long-term outcomes.